The Effect of Mediation Work Engagement to Procedural Justice and Organizational Learning on the Innovative Behavior - Sari, Fara Kartika; Palupiningdyah, Palupiningdyah (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of procedural fairness and organization learning on innovative behavior through work engagement. The population in this study were all batik craftsmen in Semarang City IKM Batik, totaling 165 people. Based on this population 117 respondents were taken by proportional random sampling technique. Data collection in this study used a questionnaire, observation and interviews. The analytical method used is SPSS IBM Statistics 25. The results of this study indicate that procedural justice has positive and significant influence on innovative behavior, organizational learning can have a positive and significant effect on innovative behavior and work engagement, work engagement can have a positive and significant effect on innovative behavior, then work engagement can mediate the positive influence of procedural justice and organizational learning on innovative behavior. The conclusion of this research is procedural fairness,organizational learning and work engagemEnt can increase innovative behavior. Furthermore work attachment can mediate the influence of procedural fairness and organization learning on innovative behavior. Suggestions for IKM batik management are to have emotional closeness such as the availability of leaders to listen to the complaints of employees, the existence of activities such as workshops and exhibitions on a regular basis to trigger increased knowledge so that it is easier to create new ideas.